Optimal timing of delayed excretory phase computed tomography scan for diagnosis of urinary extravasation after high-grade renal trauma. Issue 2 (February 2019) - Keihani, Sorena; Putbrese, Bryn E.; Rogers, Douglas M.; Patel, Darshan P.; Stoddard, Gregory J.; Hotaling, James M.; Nirula, Raminder; Luo-Owen, Xian; Mukherjee, Kaushik; Morris, Bradley J.; Majercik, Sarah; Piotrowski, Joshua; et al.
Abstract : BACKGROUND: Excretory phase computed tomography (CT) scan is used for diagnosis of renal collecting system injuries and accurate grading of high-grade renal trauma. However, optimal timing of the excretory phase is not well established. We hypothesized that there is an association between excretory phase timing and diagnosis of urinary extravasation and aimed to identify the optimal excretory phase timing for diagnosis of urinary extravasation. METHODS: The Genito-Urinary Trauma Study collected data on high-grade renal trauma (grades III-V) from 14 Level I trauma centers between 2014 and 2017. The time between portal venous and excretory phases at initial CT scans was recorded. Poisson regression was used to measure the association between excretory phase timing and diagnosis of urinary extravasation. Predictive receiver operating characteristic analysis was used to identify a cutoff point optimizing detection of urinary extravasation. RESULTS: Overall, 326 patients were included; 245 (75%) had excretory phase CT scans for review either initially (n = 212) or only at their follow-up (n = 33). At initial CT with excretory phase, 46 (22%) of 212 patients were diagnosed with urinary extravasation. Median time between portal venous and excretory phases was 4 minutes (interquartile range, 4–7 minutes). Time of initial excretory phase was significantly greater in those diagnosed with urinary extravasation. Increased time to excretory phase was positively associated with finding urinary extravasation at the initial CT scan after controlling for multiple factors (risk ratio per minute, 1.15; 95% confidence interval, 1.09–1.22; p < 0.001). The optimal delay for detection of urinary extravasation was 9 minutes. CONCLUSION: Timing of the excretory phase is a significant factor in accurate diagnosis of renal collecting system injury. A 9-minute delay between the early and excretory phases optimized detection of urinary extravasation. LEVEL OF EVIDENCE: Diagnostic tests/criteria study, level III.